Dissemination of Chest Compression–Only Cardiopulmonary Resuscitation and Survival After Out-of-Hospital Cardiac Arrest. Issue 5 (4th August 2015) - Iwami, Taku; Kitamura, Tetsuhisa; Kiyohara, Kosuke; Kawamura, Takashi
Abstract : Background—: The best cardiopulmonary resuscitation (CPR) technique for survival after out-of-hospital cardiac arrests (OHCAs) has been intensively discussed in the recent few years. However, most analyses focused on comparison at the individual level. How well the dissemination of bystander-initiated chest compression–only CPR (CCCPR) increases survival after OHCAs at the population level remains unclear. We therefore evaluated the impact of nationwide dissemination of bystander-initiated CCCPR on survival after OHCA. Methods and Results—: A nationwide, prospective, population-based, observational study covering the whole population of Japan and involving consecutive OHCA patients with resuscitation attempts was conducted from January 2005 through December 2012. The main outcome measure was 1-month survival with favorable neurological outcome. The incidence of survival with favorable neurological outcome attributed to types of bystander CPR (CCCPR and conventional CPR with rescue breathing) was estimated. Among 816 385 people experiencing OHCAs before emergency medical services arrival, 249 970 (30.6%) received CCCPR, 100 469 (12.3%) received conventional CPR, and 465 946 (57.1%) received no CPR. The proportion of OHCA patients receiving CCCPR or any CPR (either CCCPR or conventional CPR) by bystanders increased from 17.4% to 39.3% ( P for trend <0.001) and from 34.6% to 47.3% ( P for trend <0.001), respectively. The incidence of survival with favorable neurological outcome attributed to CCCPR per 10 million population significantly increased from 0.6 to 28.3 ( P for trend=0.010), and that by any bystander-initiated CPR significantly increased from 9.0 to 43.6 ( P for trend=0.003). Conclusion—: Nationwide dissemination of CCCPR for lay-rescuers was associated with the increase in the incidence of survival with favorable neurological outcome after OHCAs in Japan. Abstract : Supplemental Digital Content is available in the text.